The Effect of Aminophylline on Urine Output and Fluid Balance after a Single Dose in Children Admitted to the Pediatric Cardiac Intensive Care Unit - Loomba, Rohit S.; Uppuluri, Sruti; Chandra, Priya; Yousef, Faeeq; Dorsey, Vincent; Farias, Juan S.; Flores, Saul; Villarreal, Enrique G. (Journal of Pediatric Intensive Care, 2022)
The purpose of this retrospective study was to investigate the effects of a single dose of aminophylline on urine output and fluid balance in children admitted to the cardiac intensive care unit. A retrospective study was performed to compare variables of interest before and 24 hours after aminophylline administration in children under the age of 18 years who were admitted to the cardiac intensive care unit at our institution from January 2011 onwards. Variables of interest included age, weight, aminophylline dose, concurrently administered diuretics, specific hemodynamic parameters, and blood urea nitrogen and creatinine levels. Variables such as urine output and fluid balance were measured through a binary endpoint. Data were compared in a paired fashion and continuous variables were compared through paired t-tests. Analyses were conducted using SPSS Version 23.0. A total of 14 patients were included in the study. There was no significant change in hemodynamic parameters or creatinine levels before and after intravenous aminophylline administration of 5 mg/kg. There was a significant difference in urine output, fluid balance, and blood urea nitrogen levels from the baseline value. Concurrent usage of diuretics did not show significant association with a difference in urine output or fluid balance from baseline. No significant adverse reactions were noted 24 hours after administration of aminophylline. Use of aminophylline dosed at 5 mg/kg is safe and leads to improvement in urine output and fluid balance without negatively impacting systemic oxygen delivery or renal filtration function.
Keywords: pediatric; cardiac intensive care; xanthine; aminophylline